Evaluating the Effectiveness of a Victim Impact Intervention Through the Examination of Changes in Dynamic Risk Scores. (February 2015) - Baglivio, Michael; Jackowski, Katherine
The current study examines changes in assessed criminogenic needs/dynamic risk factors of juvenile offenders participating in a victim impact delinquency intervention. Three hundred twenty juvenile offenders in residential placement were randomly assigned to either participate in a victim impact curriculum or to a control group receiving a minimal substitute. Comparison of means was used to examine changes in criminogenic domains using an actuarial risk/needs assessment. Results demonstrate significant reductions in subscales of the assessment instrument for youth assigned to the intervention compared to the control group in the intent-to-treat analysis. Additional significant reductions in subscale scores occurred for youth completing the intervention. The findings demonstrate the ability of a specific intervention to reduce risk in criminogenic domains related to offending behavior and illustrate the importance of reassessment over time. Policy implications are discussed.